Narrative Review : Ekstrak Daun Bangkal (Nauclea subdita .Merr) Terhadap Paru-Paru Hewan Uji yang Terpapar Polusi Udara Akibat Kebakaran Hutan - Shofi Maulana; Muhammad Rifqi Dharmawan; Wanda Nisa Pratiwi; Iwan Yuwindry (LPPM Universitas Sari Mulia, 2020)
Forest fires occur almost every year in Indonesia, especially during the extreme dry season. Forest fires were anticipated in advance, but fires also continued. Haze from forest fires causes disturbances which cause health problems in the community, especially respiratory problems as a result. The main objective of this review article is to determine the efficacy of extracts of bangkal leaf (Nauclea subdita .Merr) as a treatment for Acute Respiratory Infection (ARI), so that it can support the government in reducing the incidence of Acute Respiratory Tract Infection (ISPA) due to forest fires. The method used in writing this article is Narrative Review, which is a literature search both nationally and internationally through indexed journal sites such as PubMed and Google Scholar. The results obtained after reviewing the article show that the extract of bangkal leaf (Nauclea subdita .Merr) can be efficacious as Treatment of Acute Respiratory Infection (ARI) because it contains flavonoids which can be used as antioxidants. The conclusion of the review article conducted by researchers about forest fires which can cause problems in the respiratory tract can be overcome with leaf extract (Nauclea subdita .Merr) as a natural treatment to treat Acute Respiratory Infection (ARI).